2001
DOI: 10.1038/sj.gene.6363750
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterisation of the distal 5′ flanking region of the human interleukin-10 gene

Abstract: Interleukin-10 (IL-10) is an important immunoregulatory cytokine. The recent characterisation of the proximal 5' flanking region of IL-10 led to the identification of the promoter region. Two polymorphic dinucleotide repeats and 10 single nucleotide polymorphisms (SNPs) have been identified and suggested to be useful genetic markers in several diseases. We have sequenced a further 5275 bp from -9296 to -4021 of the distal part of the 5' flanking region of the human IL-10 gene from the cosmid clone pWE15-4/11. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 70 publications
(96 reference statements)
1
35
0
Order By: Relevance
“…Direct sequencing of the heteroduplex samples and one homoduplex as a reference for each fragment led to the identification of 16 sequence variations (Table 1). Most of them had been previously, identified in other studies 14,[17][18][19][20][21] with the exception of four SNPs located at positions À1270, +3814, +4123 and +4230 (Table 1).…”
Section: Search Of New Snpsmentioning
confidence: 89%
See 1 more Smart Citation
“…Direct sequencing of the heteroduplex samples and one homoduplex as a reference for each fragment led to the identification of 16 sequence variations (Table 1). Most of them had been previously, identified in other studies 14,[17][18][19][20][21] with the exception of four SNPs located at positions À1270, +3814, +4123 and +4230 (Table 1).…”
Section: Search Of New Snpsmentioning
confidence: 89%
“…This distance does not exclude the IL10 gene since peaks of linkage in complex diseases only define a confidence interval for the location of a gene and, therefore, susceptibility genes may map near peaks of linkage rather than directly under them. 13 Different polymorphisms were identified both in the 5' flanking region [14][15][16][17][18][19][20] and, more recently, in the transcribed region 21 of the IL10 gene including two microsatellites at position À4000 (IL10 15 ) and À1100 (IL10 16 ). One of the two microsatellites, IL10.G, has been shown to be associated to SLE by three independent studies, including ours [22][23][24] although this was not supported by a fourth work.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Changes in the IL-10 gene expression were suggested to be mainly transcriptional and several factor-binding sites that might be involved in the regulation of IL-10 were identified in the IL-10 promoter. [21][22][23][24] The À1087 single nucleotide polymorphism (SNP) is located in one of these sites that was associated with differences in IL-10 gene expression [25][26][27] and the GG genotype of the À1087 SNP was found to be associated with high levels of IL-10 production. 26,27 Recently, we reported that the PU.1, Spi-B and Sp1transcription factors bound to the À1087 SNP in Bcells.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Several factor-binding sites that might be involved in the regulation of IL-10 were identified in the IL-10 promoter. [20][21][22] The IL-10 promoter contains several single nucleotide polymorphisms (SNPs) among which the -1087 G/A SNP (sometimes referred to as À1082 G/A) was associated with differences in IL-10 promoter activity and IL-10 production. [23][24][25][26][27][28][29] Results of studies on the influence of the -1087 SNP on the IL-10 production in different cell types, 23,[25][26][27][28][29] however, are conflicting.…”
Section: Introductionmentioning
confidence: 99%